Comparison of Hematological and Biochemical Parameters of Clinically Healthy Buck Kid of Saanen, Sapera, and Ettawa Crossbred in Indonesia. Issue 1 (March 2021) - Sarmin,; Widiyono, I; Anggraeni, D
Abstract: The Saanen goat has adaptation abilities and is used for genetic improvement through crossbreeding programs with Ettawa breeding to produce Sapera goats in Indonesia. The development requires support for data to determine health and metabolic status. Sixteen juvenile buck goats aged 4-6 months, comprising five Saanen, seven Sapera, and four Ettawa crossbred goats, were used in this study. Blood was collected aseptically through the jugular vein for hematology and biochemical analyses. There were no statistically significant variations in most hematological and biochemical variables, except MCH, MCHC, and P-LCR. MCH in juvenile bucks of both Saanen (40.26 ± 6.94 ρg) and Sapera goats (37.96 ± 6.24 ρg) were lower than that in juvenile bucks of the Ettawa crossbred goats (61.63 ± 19.74 ρg). MCHC in juvenile bucks of both Saanen (40.96 ± 6.82 g/dL) and Sapera goats (37.01 ± 6.72 was lower than that in juvenile bucks of Ettawa crossbred goats (61.18 ± 23.15 g/dL). P-LCR in juvenile bucks of Ettawa crossbred goats (41.30% ± 10.95%) was significantly lower than that in juvenile bucks of both Saanen (63.48 ± 8.98%) and Sapera goats (69.00 ± 12.00%). Besides, no statistically significant variations were observed in enzyme, iron, lipid, and electrolyte activity in all three breeds.